Hair Follicle Nevus of the Abdominal Skin: An Unusual Extracephalic Presentation. Issue 3 (6th March 2014) - Jedrych, Jaroslaw; Akilov, Oleg; Gehris, Robin; Ho, Jonhan
Abstract Hair follicle nevus (HFN) is a rare hamartoma typically diagnosed on the face of infants, where it may clinically mimic an accessory tragus. We report a 6‐month‐old boy who presented with a congenital fleshy, bilobed papule in the midline of his upper abdomen that upon excision was classified as an HFN based on detailed histopathologic examination. Our report documents a previously undescribed extracephalic location of the HFN and therefore expands the spectrum of clinical presentations of this rare hamartoma.